Superior keratoconus with hydrops - Tananuvat N. (2014)
Superior keratoconus is a rare form of keratoconus, in which the corneal apex is atypically superior. We report a 32-year-old man who presented with corneal hydrops in his right eye. Ophthalmic examination revealed corneal edema with Descemet's break involving the superior part of his right cornea. Superior steepening in the left cornea demonstrated by corneal topography was consistent with subclinical keratoconus. © Springer Science+Business Media B.V. 2008.